PENGARUH KOMUNIKASI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA KARYAWAN PT. RESOURCE EQUIPMENT INDONESIA - Pasoloran, Octavyani; Anam, Soleh; Hendrawan, Yudhi (MEDIA RISET EKONOMI [MR.EKO], 2026)
The purpose of this study was to determine the effect of communication, motivation, and work environment on job satisfaction of employees of PT. Resource Equipment Indonesia, with 48 respondents, this research method uses quantitative methods. Collecting data by means of observation and distributing questionnaires through google form. The data analysis technique used is multiple linear analysis by performing instrument tests, classical assumption tests, and partial hypothesis testing (t-test). The results showed that the variables of communication, motivation, and work environment partially had a positive and significant effect on job satisfaction for employees of PT. Resource Equipment Indonesia. Keywords: Communication, Motivation, Work Environment, Job Satisfaction.